Design of a thermoforming process for a semi-crystalline polymer - Farah Amira, Mohd Ghazali (2017)
The use of thermoformed plastic products continues to escalate each year causing vast productions of these plastic manufactured merchandises. A low-cost in design and tooling for the production of thermoformed products compared to injection and blow moulded products has become a major factor in which the former is preferred over the latter; in cases of manufacturing simple to complex shapes of plastic products. As plastic productions continue to grow, issues in defects of these parts begin to spread whereby causing low quality thermoformed plastic products to be manufactured. The issues of the defects include incomplete forming and non-uniform wall-thickness distribution of the thermoplastic product which leads to the decreasing the high quality of the thermoformed plastic product. The objective of this research is to design and develop a thermoforming process for the production of a thermoformed plastic part using a positive mould whereby implementing drape forming technique and venting features. A semi-crystalline polymer material, Polypropylene (PP) is heat-softened and drawn onto a positive mould with the assistance of a constant pressure of 20 kPa. Experimental investigations and visualisation observations were carried out in the understanding material behaviour of the polymer material when treated to elevated temperature during the heating of the plastic sheet prior to forming. ANSYS ® Polyflow simulation software was used to compute the modelling of the thermoforming process simulation. The total amount of time of the simulation is 2.6 seconds. Post-thermoforming, the thickness of the thermoforming plastic sheet in the regions in which the venting systems are allocated (region AB and DE) only decreased 22.5% and 37.5% respectively. In regions AB and DE, air is removed through the venting system allowing the plastic sheet to conform onto the mould. The material distribution on these regions are better distributed compared to without using venting system.